Steeple ebook - Allison, John (Steeple (2019)., 2020)
A supernatural tale of friendship, the devil, and moral gray areas.Two women with wildly different worldviews become unlikely friends as they navigate the supernatural happenings in a sleepy coastal parish--and soon find themselves forced to choose sides in the war between good and evil, facing demons, curses, and a miniature Rapture!The latest graphic novel from John Allison, author of Giant Days!Collects issues #1-#5 of Dark Horse Comics series Steeple.